Clinical and research applications of a brain tumor tissue bank in the age of precision medicine. (28th February 2019) - Snyder, James; Poisson, Laila M; Noushmehr, Houtan; Castro, Ana V; deCarvalho, Ana C; Robin, Adam; Mukherjee, Abir; Lee, Ian; Walbert, Tobias
Marked progress has been made recently in the treatment of patients with central nervous system (CNS) tumors, especially gliomas. However, because of the relative rarity of these tumors compared with other malignancies, advances in the molecular/genetic analysis leading to future targeted treatments rely on systematic, organized tissue banking. Several large multi-institutional efforts have utilized major tissue banks that have yielded valuable information that may lead to a better understanding of the pathogenesis of CNS tumors. This manuscript portrays best practices for the establishment and maintenance of a well-organized CNS tumor bank. In addition, annotation for clinical and research needs is explained. The potential benefits to clinical care, as well as basic science and translational research are also described.